2006
DOI: 10.1111/j.1440-1681.2006.04490.x
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine Pathway Metabolism in Patients With Osteoporosis After 2 Years of Drug Treatment

Abstract: 1. Metabolism of tryptophan along the oxidative pathway via kynurenine results in the production of quinolinic acid and kynurenic acid, which can act on glutamate receptors in peripheral tissues. We have now measured the concentrations of kynurenine pathway metabolites in the plasma of patients with osteoporosis before treatment with drugs, throughout and after 2 years of treatment with the drugs raloxifene or etidronate. Oxidative stress was assessed by measuring levels of the lipid peroxidation products malo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 64 publications
5
68
1
Order By: Relevance
“…58,59 These results might be pointing to a possible beneficial role of 3-HAA in humans and the presence of a clinically important alternative KP pathway for 3-HAA generation (Figure 1). The notion that 3-HAA per se is not necessarily toxic is supported by our mouse injection studies, which showed no evidence of cell death beyond what was evident in vehicle-injected brains ( Figure 8C; see also Supplemental Figure S1 at http://ajp.amjpathol.org).…”
Section: Discussionmentioning
confidence: 98%
“…58,59 These results might be pointing to a possible beneficial role of 3-HAA in humans and the presence of a clinically important alternative KP pathway for 3-HAA generation (Figure 1). The notion that 3-HAA per se is not necessarily toxic is supported by our mouse injection studies, which showed no evidence of cell death beyond what was evident in vehicle-injected brains ( Figure 8C; see also Supplemental Figure S1 at http://ajp.amjpathol.org).…”
Section: Discussionmentioning
confidence: 98%
“…Oxidative stress, resulting from excessive levels of reactive oxygen species (ROS), represents a major cause of cellular damage and death in pathological conditions including osteoporosis, in which oxidative stress is associated with increased bone resorption and low bone mass (Forrest et al, 2006;Baek et al, 2010;Yilmaz and Eren, 2009;Sanchez-Rodriguez et al, 2007a;Varanasi et al, 1999). It was reported that blood 8-hydroxy-2'-deoxyguanosine (8-OH-dG), a marker of oxidative stress, was associated with osteoporosis in postmenopausal women (Baek et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This is associated with distinct increases in blood levels of oxidative stress markers (4)(5)(6). The main oxygen species responsible for oxidative stress are hydrogen peroxide (H 2 O 2 ), the free radical superoxide anion (O 2 -) and the hydroxyl radical (OH -).…”
Section: Introductionmentioning
confidence: 99%